Intercultural communication - Cai, Deborah A.; Sage eBooks (Los Angeles, [Calif.] : SAGE, 2010)
Intercultural research finds its roots mainly in anthropology psychology and sociology. However many scholars draw mostly from a relatively recent body of work. This title reflects both the classic works as well as the recent works. It examines a wider and more interdisciplinary range of literature that has influenced this field.
Specialized.
Description based on print version record.
Includes bibliographical references.
Keywords: Intercultural communication; Electronic books